The Role of Ethnocentrism and Animosity on Willingness to Buy Chinese Products; Does Foreign Product Judgement Mediate the Relation? - Wijayanti, Cynthia Anna; Elicia, Evelyn (Klabat Journal of Management, 2024)
Due to long-standing anti-Chinese sentiments and prior research highlighting Indonesia's high ethnocentrism, this study aims to delve deeper and explore whether Indonesian Consumer Ethnocentrism and Animosity impact their willingness to purchase Chinese products, with foreign product judgment serving as an intervening variable. This study focuses on Chinese products and involves Indonesian consumers in the Jabodetabek region familiar with purchasing goods made in China. The research employed a non-probability judgment sampling technique and used an electronic questionnaire to collect responses from 150 participants. Utilizing the Partial Least Square-Structural Equation Modeling (PLS-SEM) method with SmartPLS software. The findings indicate that Indonesian Consumer Ethnocentrism and Consumer Animosity did not negatively affect the willingness to buy Chinese products. Additionally, no mediating effect was observed through Foreign Product Judgment in these relationships. However, the research revealed Indonesian Consumer Ethnocentrism's significant and positive influence on Indonesian Consumer Animosity. Regarding managerial implications, this study recommends that domestic companies highlight local cultural values, while multinational corporations should consider localizing their products to enhance consumer familiarity.